Problems in implementation of ISO 9001 quality management system among Malaysian contractors - Tan, Chin Keng; Yeoh, Kah Ching (2010)
The government of Malaysia strongly encourages the Malaysian contractors to obtain ISO 9001 certification. The certification is to produce contractors that practice standards that are recognized not only in Malaysia but also abroad. However, the number of ISO 9001 certified contractors in Malaysia is very low if compared with the total number of contractors in the country. The objectives of this research are to determine the human-related problems associated with the implementation of ISO 9001 quality management system based on the perceptions of the ISO 9001 certified contractors and propose solutions for those problems. A questionnaire survey was conducted to achieve the research objectives. Samples for the survey were drawn from the list of ISO 9001 certified contractors in Malaysia. A total of forty-four (14.47% from the total questionnaire sent) responses received. The major human-related problems identified from the results a questionnaire survey are staff’s lack of experience to exercise the system, lack of commitment of staff, and lack of initiative among staff. It is suggested that in order to enhance the experience of staff for the ISO 9001 quality management system, appropriate training courses to be provided to the relevant staff. In addition to that, the organizations should recruit more staff which are capable and experience on ISO 9001 quality management system. As for the problems of lack of commitment and initiative among staff towards the implementation of the quality management system, it is recommended that quality culture should be inculcated in construction organizations and positive enhancement such as rewarding staff for their good performance and compliance to the ISO 9001 quality management system should be taken.